2011
DOI: 10.1089/gtmb.2010.0098
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Black Women for a Study of Inherited Breast Cancer Using a Cancer Registry–Based Approach

Abstract: This is the first study conducted through a State Cancer Registry, in which the primary goal was to recruit participants for genetic counseling and testing for inherited breast cancer. In contrast to many prior studies, our results suggest that young black women with breast cancer are interested in participating in genetics studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Including women from non-clinical settings is important because optimal genetic counseling and testing practices will involve engaging individuals who may not be interacting with the healthcare system or with providers who would talk to them about genetic testing [31, 34, 52, 60]. Consistent with previous research done by Pal and colleagues, the women in this sample had a high interest in BRCA1/2 testing, despite limited exposure [48]. …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Including women from non-clinical settings is important because optimal genetic counseling and testing practices will involve engaging individuals who may not be interacting with the healthcare system or with providers who would talk to them about genetic testing [31, 34, 52, 60]. Consistent with previous research done by Pal and colleagues, the women in this sample had a high interest in BRCA1/2 testing, despite limited exposure [48]. …”
Section: Discussionmentioning
confidence: 56%
“…Still, strategies to improve accrual of Black women into breast cancer genomic research have had limited success, and data on determinants of participation are equivocal [16, 47, 48]. One kindred study found that Black women with family histories of breast or ovarian cancers were interested in genetic counseling and testing for BRCA1/2 [23]; however, multiple studies with Black/White samples have shown that Black women in the general population as well as those with a recent breast cancer diagnosis have lower awareness of, interest in, and uptake of BRCA1/2 counseling and testing than their White counterparts [3, 36, 4951].…”
Section: Introductionmentioning
confidence: 99%
“…Through protocols approved through the Institutional Review Boards at the University of South Florida and the Florida Department of Health, recruitment of Black women was initiated in 2012 as previously described, 29, 30 and that of White and Hispanic women was initiated in 2014. Using information on all eligible participants released by the Florida State Cancer Registry, contact was attempted among all Black and Hispanic women in the sampling frame and in a random sample of White women (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited 6-18 months after their diagnosis using previously described state-mandated recruitment methods [22], which consisted of 2 mailings, 3 weeks apart, including a ‘telephone response card’ to give potential participants the option to either decline (i.e., indicating that they did not wish to be contacted by phone) or express interest in participation (i.e., indicating that they were interested in having the study team call them to follow-up). If no response was received within 3 weeks of the second mailing, a member of the study team attempted to contact the potential participant by telephone to explain the study and determine interest in participation.…”
Section: Methodsmentioning
confidence: 99%